Application of Nursing Care in Patients With Fluid and Electrolyte Needs in Hemodialisa Room, Labuang Baji Makassar’s Hospital - Sulaiman, St. Suarniati (Universitas Sulawesi Barat, 2019)
Chronic Kidney Disease (CKD) is a failure of kidney function so that it is unable to run its function properly, causing decreased glomerular filtration gradually, thus undergoing hemodialysis therapy. According to the WHO in 2017 which states that GGK disease ranked 12th highest mortality rate. And according to the results of riskesdas in 2013, South Sulawesi is ranked third with a prevalence of 0.3%. Handling efforts to decrease the volume of fluid by means of fluid restriction affects the patient's survival. This study aims to describe nursing care in patients. N with GGK in fulfillment of fluid requirement in Hemodilisa Room of RSU Labuang Baji Makassar, using descriptive method with case study approach. The results of this study indicate excess fluid volume characterized by grade 2 edema in the extremities, abdominal bloating and frequent burping, thirst, olguria, anemia and azotemia. The application of nursing care is done to monitor the intake output and fluid restriction so that no excess fluid volume can be concluded that monitoring of intake output and fluid restriction in GGK patients undergoing HD can effectively decrease the density of edema and weight. It is advisable to the nurse to monitor the patient's intake output for 24 hours and provide education for the implementation of home care in preventing excess fluid volume.